Model reduction for linear differential inclusions: robustness and time-variance - Scarciotti,G; Teel,AR; Astolfi,A (IEEE, 2017)
This paper deals with the problem of modelreduction by moment matching for linear differential inclusions.The problem is formally formulated and the notions of moment-set, perturbed moment trajectory, approximate reduced ordermodel and robust reduced order model are introduced. Twosets of results are presented. The first part of the paper dealswith robustness of the reduced order models with respect toinput perturbations. Exploiting this result an enhanced modelreduction scheme for linear differential equations is presented.In the second part of the paper we focus on the problem ofmodel reduction by moment matching for time-varying systemsdriven by time-varying signal generators. Finally, these two setsof results are used to solve the problem of model reductionfor linear differential inclusions. The results are illustrated bymeans of numerical examples.